Quantifying the surface modification induced by the argon cluster ion bombardment of KGd(WO4)2: Nd single crystal - Korobeishchikov, N. G.; Nikolaev, I. V.; Atuchin, Victor V.; Prosvirin, Igor P.; Kapishnikov, A. V.; Tolstogouzov, A.; Fu, D. J. (Materials research bulletin)
The damage in an inorganic single crystal surface caused by gas cluster ion bombardment is still an open issue. In this work, the influence of the kinetic energy per atom in the clusters E/N on the physicochemical structure of KGd(WO4)2:Nd single crystals was evaluated using XPS, Raman spectroscopy and XRD techniques. The highenergy mode with an energy per atom in the cluster E/N of about 100 eV provides a sufficient sputtering efficiency, while the low-energy mode with an energy of a several eV provides the minimal surface damage. The results revealed no substantial damage to the subsurface crystal structure after the cluster bombardment processing. Nevertheless, the unexpected increase in the relative concentration of O atoms by 12% and depletion of K atoms by a factor of 2 in the subsurface layer of KGd(WO4)2:Nd crystals were detected. The features of surface sputtering of inorganic single crystals at different E/N-modes are discussed.